Adverse effects of inappropriate use of dietary supplements - Santos, Clistenis Clênio Cavalcante dos; Oliveira, Kelvin Nathan dos Santos; Chaves, Eliel dos Santos (Research, Society and Development, 2023)
Along with exercising, it's clear that people are concerned about improving their diets for a variety of reasons, whether it's to gain a leaner body, help with illness, or lead to a healthier old age. Therefore, the following research aims to highlight the risks of irrationally using dietary supplements. The searches were carried out through the following databases: Lilacs, Scielo, Pubmed and CAPES. Articles published between the years 2012 and 2022 were used. Among the 63 articles chosen through the abstract, after reading them, only 20 that alluded directly to the theme were used for the research. The results indicate that the use of nutritional supplements has been associated with the following benefits: increase in resistance, decrease in body fat, increase in muscle mass, minimization of the risk of diseases, muscle restoration or increase in performance during physical activity, but the abuse of these potentiating substances results in less time are not completely harmless. Daily advertisements convince people of the need for food supplements. The observed misuse of dietary supplements and medications in Brazil can be explained by the lack of strict legislation that prohibits their sale without a medical prescription or a professional nutritionist. In this way, pharmacists play an important role in providing guidance on its use, advising on available options, conditions of use and administration. Generating the promotion, protection and rehabilitation, promoting health and well-being.